TECHNIKI OBRAZOWANIAThe role of precise diagnosis of the clinical problem of congenital heart disease in the form of transposition of the great arteries (l-TGA) based on own clinical material - Głowacki, Jan; Obersztyn, Anna; Wasilewski, Jarosław; Obersztyn, Maciej; Karwot, Blandyna; Kusa, Jacek; Miszalski-Jamka, Karol; Osadnik, Tadeusz; Iwiński, Janusz; Białkowski, Jacek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Introduction: Corrected transposition of the great arteries (1-TGA) is a rare innate developmental defect of the circulatory system. Aim: The aim of the study is to take a closer look at the complex heart disease 1-TGA and to present an undoubtedly serious clinical problem caused by this defect based on two cases, the first diagnosed early, treated properly, and the second, diagnosed too late, in adulthood, not properly treated before. Material and Methods: Two cases of 1-TGA are presented. In the first case, the defect was recognized in the neonatal period and after two operations (on the second day of life and at the age of 5 years) the patient was under constant clinical observation. The second case, a 36-year old patient, was admitted to the cardiology ward due to severe circulatory insufficiency. His innate heart defect had not been diagnosed properly before, so it had not been treated properly. Due to heart insufficiency and advanced pulmonary hypertension, the only method of treatment was a heart transplant. Discussion: The notion of corrected transposition of the great arteries is inseparably connected with the concept of ventricle inversion. This defect can be of isolated character (10%). The most common anomalies accompanying the defect are: structural diseases of systemic valve (70-90%), ventricular septal defect (79%) and stenoses of outflow route of various degree. The most useful and sometimes sufficient means for establishing a diagnosis is echocardiography, done as early as in the prenatal period. In some cases, it can be helpful or even essential to extend the diagnosis by computed tomography, magnetic resonance or diagnostic heart catheterization. The natural course of the disease depends mostly on its configuration and accompanying diseases. The moment of making a decision about cardiosurgical intervention and the type of suggested surgery is inseparably related to the accompanying diseases.